REKONDISI HEAD MESIN FRAIS FEHLMANN PICOMAX 20 DI LABORATORIUM TEKNIK MESIN POLITEKNIK MANUFAKTUR NEGERI BANGKA BELITUNG - Bindara, Bindara; Muhamad, Muhamad; Masdani, Masdani; Feriadi, Indra (Politeknik Manufaktur Negeri Bangka Belitung, 2025)
This study aims to perform a reconditioning of the Fehlmann Picomax 20 milling machine head in the Mechanical Engineering Laboratory of the Bangka Belitung State Polytechnic of Manufacturing. The main damage to the machine head was caused by the accumulation of swarf and frozen grease in the gear and machine column sections. The reconditioning process includes data collection, problem identification, root cause failure analysis using the Root Cause Failure Analysis (RCFA) and 5-Why Analysis methods, repair planning, the repair process, and testing after the repair has been carried out. The test results show that the machine head has been able to function again according to its specifications, including in functional testing, machine performance testing, and column straightness testing. In addition, preventive maintenance has been designed to prevent similar damage from recurring in the future. This project is expected to improve the effectiveness of student learning and extend the operational life of the machine.